CARACTERÍSTICAS DEMOGRÁFICAS, CLÍNICAS, CIRÚRGICAS E O GRAU DE HUVOS DOS OSTEOSSARCOMAS TRATADOS EM 11 ANOS EM SÃO LUIS-MA - Martins Filho, Paulo Pereira Fontes (2012)
Introduction: The Huvos grading system is considered one of the most important prognostic factors for survival in patients with osteosarcoma Objective: Analyze the Huvos grading system with the demographic, clinical and surgical variables, describing the epidemiological profile of patients with osteosarcoma, with rates of frequency and death. Methods: Through of data obtained from medical records were studied 83 cases of osteosarcoma treated at University Hospital of Federal University of Maranhão - HUUFMA and Oncology Institute of Maranhão - IMOAB from march 2000 to march 2011. Inclusion criteria were cases of patients any of age with localized high grade osteosarcoma in the appendicular skeleton, were not included incompletes cases and cases with multiple lesions and or the axial skeleton. The statistical analysis was based on Fisher's exact test with a significance level of p < 0.05 between the independent variables and the dependent variable Huvos grade . Results: the sample was 83 cases of high grade osteosarcoma, 67% was male, 82% was in lesser than or equal to 20 years, 63.8% from interior areas of Maranhão, 79.4% of cases involve the knee, 69% was osteoblastic histologic variant of osteossarcoma, and 60% with tumors greater than 12 cm in largest axis. The surgical treatment most frequently performed was the amputation of the affected limb with 63.8%. About 96.5% reported surgical margins were tumor-free margins. The Huvos grading system: 27% with grade I, 50% with grade II, 23% with grade III and no one grade IV. The frequency rate of osteosarcoma was 6.9 new cases per year. And the death rate of osteosarcoma patients was 61%. Conclusion: Osteosarcoma shows high local deaths rate and with high frequency rate. And the Huvos grading system is statistically related to the presence of pulmonary metastasis (p=0,025) and death (p=0,015) of patients with osteossarcoma.